Đáp án: 1,669
Giải thích các bước giải: $(3 - x)^{2}$= ($\frac{121}{100}$)$^{3}$
=> $(3 - x)^{2}$ = ($\frac{121}{100}$)$^{2}$. $\frac{121}{100}$
=> $(3 - x)^{2}$ : ($\frac{121}{100}$)$^{2}$ = $\frac{121}{100}$
=> $[(3 - x)^{}$ : $\frac{121}{100}$]$^{2}$ = $\frac{121}{100}$
=> $[(3 - x)^{}$ : $\frac{121}{100}$]$^{2}$ = $(\frac{11}{10})$$^{2}$
=> $(3 - x)^{}$ : $\frac{121}{100}$ = $\frac{11}{10}$
=> (3 - x) = $\frac{11}{10}$ . $\frac{121}{100}$
=> (3 - x) = $\frac{1331}{1000}$
=> x = 3 - $\frac{1331}{1000}$
=> x = $\frac{1669}{1000}$
=> x = 1,669.